Teachers’ Perceptions on E-Media Adoption in Basic Electronics Technology - Galileo A. Toledo (Randwick International of Education and Linguistics Science Journal, 2021)
This paper presents the extent of adopting E-media in the Electronics Technology curriculum as an alternative instructional tool in developing the students’ competencies in measuring instruments, symbols, and circuit diagrams. The study found out that the five competencies under Safety were all given a descriptive rating of Very Satisfactory. This implies that the instructors observed the highest degree of safety protocols in their respective shops in the activity's conduct. The adoption of E-media in electronics, technology classes serve to improve students' learning capability to master the subject matter. Using the E-media facilities as an instructional tool, it facilitated the learning process. E-media's adoption as an additional instructional tool supplemented the identified competencies in the safety shop subject. It allows students to learn the basic principles of electronics technology, whereby interaction is encouraged and theories are put into practice in actual hands-on activities. The study suggested that the adoption of E-media in Electrical technology classes is continually done and practiced. Regular monitoring and updating of materials are also necessary for ensuring that the use of E-media is properly implemented.